1987
DOI: 10.1104/pp.83.4.849
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Photoassimilation by the Spinach Chloroplast at Low Temperature

Abstract: Spinach chloroplasts were used to study the relationship between photosynthetic CO2 fixation and temperature from 30 to -15°C. In saturating light and high concentrations of CO2, the temperature coefficients (Q,.) above 20°C were less than 2 in the intact chloroplast. Below 15°C, the Qlo values were greater than 2 and gradually increased with decreasing (down to 0WC) temperature to approximately 4.4. Photosynthesis responded similarly to temperature in a reconstituted chloroplast preparation fortified with rib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Increases in GPP with warming were attributed to more rapid carboxylation and respiratory kinetics, represented by the low‐temperature inactivation terms in Arrhenius equations used to model the temperature dependence of CO 2 fixation (C10), R a (C22), and R h (A6). This term caused Q 10 derived from these equations to rise with lower temperatures (Grant 2014), as found in experimental studies on the temperature dependence of CO 2 fixation by Fu and Gibbs [], and of R h by Tuomi et al . [], so that sensitivity of biological reactions to temperature was greater in cooler climates.…”
Section: Resultsmentioning
confidence: 70%
“…Increases in GPP with warming were attributed to more rapid carboxylation and respiratory kinetics, represented by the low‐temperature inactivation terms in Arrhenius equations used to model the temperature dependence of CO 2 fixation (C10), R a (C22), and R h (A6). This term caused Q 10 derived from these equations to rise with lower temperatures (Grant 2014), as found in experimental studies on the temperature dependence of CO 2 fixation by Fu and Gibbs [], and of R h by Tuomi et al . [], so that sensitivity of biological reactions to temperature was greater in cooler climates.…”
Section: Resultsmentioning
confidence: 70%
“…Brtiggemann (1992) demonstrated that chilling temperatures inhibit photosynthesis by limiting the consumption of reducing equivalents and that this increased the susceptibility of the light reactions to photoinhibition. Additional experimental evidence for a slowing of the dark reactions in the cold comes from Fu and Gibbs (1987) who measured photosynthesis in intact spinach chloroplasts from -15 to 30 °C. They recorded a cold-temperature-dependent inhibition of carboxylation and concluded the cause was an increase in stromal viscosity that impaired the diffusion of substrate(s) to the RuBisCO enzyme.…”
Section: Evidence For the Overreduction Of Electron Transport During mentioning
confidence: 99%
“…The neutralized mixture was centrifuged and the increase in A340 was taken as the amount of NADPH formed. Esterification of 32p was by a method described in an earlier report (12).…”
Section: Materuils and Methodsmentioning
confidence: 99%